Age-specific health-related quality of life in disease-free long-term prostate cancer survivors versus male population controls: results from a population-based study - Adam, Salome; Doege, Daniela; Koch-Gallenkamp, Lena; Thong, Melissa S. Y.; Bertram, Heike; Eberle, Andrea; Holleczek, Bernd; Pritzkuleit, Ron; Waldeyer-Sauerland, Mechthild; Waldmann, Annika; Zeissig, Sylke Ruth; Jansen, Lina; et al. (Supportive care in cancer, 2020)
Prostate cancer (PC) and its treatment may affect PC survivors differently with respect to age. However, little is known regarding age-specific health-related quality of life (HRQoL) in PC survivors 5 years or even ≥ 10 years post-diagnosis.
Published online: 18 November 2019
Gesehen am 15.05.2020